Postfinishing mineralization of skeletal tissue in replacement gilts - R I Nicholson; G E Fitzner; Robert H Hines; Robert D Goodband; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1990)
Thirty-two crossbred gilts averaging 250 /b were selected for the experiment at the conclusion of the finishing phase. Eight of the gilts were slaughtered on d 0 to serve as a pretreatment control group. The remaining 24 gilts were assigned to three dietary treatments to provide daily 100% (14 g/d Ca and 11.3 g/d P), 150% (22.5 g/d Ca and 16.6 g/d P), and 200% (29.9 g/d Ca and 22.0 g/d P) of the Ca/P level consumed per d during the finishing phase. These gilts were slaughtered 35 d later at 291 lb. Gilts receiving 29.9 g/d Ca and 22.0 g/d P yielded ribs that had the highest values for percent ash, bending moment, and modulus of elasticity. Femurs did not differ in any bone characteristics because of treatment; however, the 3rd metacarpal bone showed the highest percent ash and greatest bending moment at the intermediate level of Ca/P.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; GF; Performance; Calcium; Phosphorus; Sow